Fabrication technique and characterization of pure BMI materials - Lim, Jia Hao (2015)
BMI composites are also slowly introduced to the marine industry as a possibility to replace metal used to build under water pipes subjected to prolonged immersion in seawater, elevated temperatures, and high levels of forces and stresses in deep sea applications. However, BMI composites have a tendency to absorb moisture when exposed to water, affecting its mechanical properties adversely. This project aims to develop an effective technique to fabricate neat BMI specimens and to characterize pure BMI materials using different mechanical tests. The fabrication process of neat BMI specimens from raw BMI blocks was developed and used to fabricate two BMI plates. One was used for dry specimen tests while one was used for moisture diffusion test and wet specimen tests. The moisture diffusion test for the fabricated BMI plate immersed in salt water of 3.5% salinity at 80°C showed a two-stage diffusion behavior and fits the Langmunir diffusion model. The Multi-Frequency Strain, Temperature Ramp DMA test showed that a higher curing temperature results in a higher Tg and improves the physical properties of pure BMI materials. The Temperature Step, Frequency Sweep DMA test allowed the 35°C master curve to be generated from the time temperature superposition model and enables the evaluation of long term reliability at different service temperatures by shifting the master curve to desired temperature using the shift factors computed for different temperatures. The flexural test conducted for both dry and wet specimens at 25°C, 200°C, and 260°C showed the degradation effects of both temperature and moisture on flexural properties of pure BMI materials below Tg. Results acquired from this project aids in characterization of pure BMI materials and contributes to the material database for use to extend its applications into the marine industry.